Comparison of Submental Blood Collection with the Retroorbital and Submandibular Methods in Mice (Mus musculus) - Regan, Rainy D; Fenyk-Melody, Judy E; Tran, Sam M; Chen, Guang; Stocking, Kim L (Journal of the American Association for Laboratory Animal Science, 2016)
Nonterminal blood sample collection of sufficient volume and quality for research is complicated in mice due to their small size and anatomy. Large (>100 μL) nonterminal volumes of unhemolyzed or unclotted blood currently are typically collected from the retroorbital sinus or submandibular plexus. We developed a third method-submental blood collection-which is similar in execution to the submandibular method but with minor changes in animal restraint and collection location. Compared with other techniques, submental collection is easier to perform due to the direct visibility of the target vessels, which are located in a sparsely furred region. Compared with the submandibular method, the submental method did not differ regarding weight change and clotting score but significantly decreased hemolysis and increased the overall number of high-quality samples. The submental method was performed with smaller lancets for the majority of the bleeds, yet resulted in fewer repeat collection attempts, fewer insufficient samples, and less extraneous blood loss and was qualitatively less traumatic. Compared with the retroorbital technique, the submental method was similar regarding weight change but decreased hemolysis, clotting, and the number of overall high-quality samples; however the retroorbital method resulted in significantly fewer incidents of insufficient sample collection. Extraneous blood loss was roughly equivalent between the submental and retroorbital methods. We conclude that the submental method is an acceptable venipuncture technique for obtaining large, nonterminal volumes of blood from mice.